(untitled) (Anclajes, 2020)
This article examines the online comments section of Nicaraguan newspaper reports on gender violence, focusing specifically on articles about Law 779: The Integral Law Against Violence Towards Women (2012). The study traces contemporary public opinion regarding gender relations, crime, and the law. The comments sections reveal that many commentators do not view gender violence as a State problem, but rather they assert that it should be handled in the family unit. This belief is bolstered by State policies that advocate for restoring family peace and harmony through dialogue. The article highlights another main complaint against Law 779 in the comments: that it inaugurates a war against men. I conclude that this perspective constitutes a refusal to cede power and privilege. These representational battles reveal ceaseless anxiety over Law 779’s ruinous effects on the family. In the end, allegations about the divisiveness of the law point to a desire for the return of traditional family narratives. Law 779 embodies several decades of women’s demands for respect, autonomy, and freedom from violence. After a rapid pendulum swing in society about Law 779, public opinion reflects extreme uncertainty and instability regarding changing expectations, both legal and social, for gendered behavior.